Mykhailo Hrushevskyi and Halychyna (1885–1894) - Raikivskyi, Ihor (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article discusses М. Hrushevskyi’s interest in Halychyna and his early association with the narodovtsi in 1885–1894 prior to his relocation to Lviv, where, in consequence of the “New Era” policy, he was invited to chair the newly created History of Ukraine Department at Lviv University. The author focuses on the young historian’s connections with the Halychian narodovtsi from the beginning of his association with the region and the publication of his first article in Dilo (The Deed), a Lviv-based newspaper, till his relocation to the capital of Halychyna